Group IV humpback whales: their status from aerial and landbased surveys off Western Australia, 2005 - Paxton, Charles G.M.; Hedley, Sharon l.; Bannister, John l. (The journal of cetacean research and management, 2020)
Single platform aerial line transect and land-based surveys of Southern Hemisphere Group IV humpback whales were undertaken to provide absoluteabundance estimates of animals migrating northward along the western Australian coast during June–August 2005. The aerial survey was designedto cover the whole period of northward migration but the resulting estimates from that survey alone could only, at best, provide relative abundanceestimates as it was not possible to estimate g(0), the detection probability along the trackline, from the data. Owing to logistical constraints, theland-based survey was only possible for a much shorter period (two weeks during the expected peak of the migration in mid-July). This paperproposes three methods that utilise these complementary data in different ways to attempt to obtain absolute abundance estimates. The aerial linetransect data were used to estimate relative whale density (for each day), allowing absolute abundance from the land-based survey to be estimatedfor the short period of its duration. In turn, the land-based survey allowed estimation of g(0) for the aerial survey. Absolute estimates of abundancefor the aerial survey were obtained by combining the g(0) estimate with the relative density estimates, summing over the appropriate number ofdays. The most reliable estimate of northward migrating whales passing the land station for the period of the land-based survey only was 4,700(95% CI 2,700–14,000). The most reliable estimate for the number of whales passing through the aerial survey region for the duration of that survey(55 days from June through to August) was 10,300 (95% CI 6,700–24,500). This is a conservative estimate because the duration of the aerial surveywas almost certainly shorter than the period of the migration. Extrapolation beyond the end of this survey was considered unreliable, but abundancefrom the estimated start of the migration to the end of the survey (87 days from mid-April to August) was estimated to be 12,800 (95% CI 7,500–44,600). The estimated number of whales depends crucially on the assumed migration and period of migration. Results for different migrationparameters are also presented. The point estimates of abundance, whilst higher than those from a previous survey in 1999 (when adjusted for surveyduration) are not significantly so. The peak of the whales’ distribution was found at c.90m water depth.